"Radio Alice and Italy's Movement of 1977: polyvocality, sonority and space". Issue 2 (3rd July 2021) - Pollard, Damien
ABSTRACT: Radio Alice was a free radio station that broadcast from 1976–1977 in Bologna, Italy, and was an integral part of the left-wing, countercultural Movement of 1977. This article contextualises the emergence of Radio Alice in relation to the Movement of 1977; the avant-garde political magazine A/Traverso, which had been published since 1975 by the collective that founded Radio Alice; and the international history of community radio. I then show how Radio Alice's approach to broadcasting drew from these three contexts in seeking to unseat the logic of capitalism and replace it with a celebration of desire. The station's practice emphasised polyvocality through the extensive use of telephone phone-ins and challenged language itself through surreal speech and non-linguistic vocalisation. I explore how this vocal practice expressed the station's countercultural politics and, drawing on the work of Adriana Cavarero and Doreen Massey, I argue that it was a practice with spatial consequences. These spatial consequences became both explicit and tangible during the 1977 Bologna riots when the station was shut down live on air. Ultimately, and most broadly, I contend that as a central component of human interrelation the voice is always already implicated in the social construction of space.